So sánh phong trào Bình dân học vụ (1945 - 1946) và Bình dân học vụ số: Sự kế thừa và chuyển hóa trong giáo dục toàn dân - Nguyễn Hồng Hà, Nguyễn Hồng Hà; Bùi Trần Khôi Nguyên, Bùi Trần Khôi Nguyên; Hoàng Khánh Linh, Hoàng Khánh Linh; Nguyễn Anh Tuấn, Nguyễn Anh Tuấn (Tạp chí Giáo dục, 2026)
Although extensive research has examined mass literacy and digital literacy initiatives in Vietnam, these movements are often analyzed separately, leaving limited attention to the continuity and transformation of their underlying educational philosophy across historical periods. Addressing this gap, this study employs a qualitative comparative approach to examine the (1945 - 1946) Binh dan hoc vu movement and the contemporary Binh dan hoc vu so initiative, focusing on policy objectives, educational content, and implementation models. The findings indicate that both movements share a common ideological foundation centered on universal access to foundational competencies as a strategy for national development. At the same time, the digital literacy initiative demonstrates clear transformations in knowledge content, technological tools, and modes of implementation, particularly through a shift from volunteer-based mobilization to a coordinated, multiactor ecosystem involving state agencies, enterprises, and community-level digitalsupport networks. By clarifying how the “Khai dan tri” philosophy has been recontextualized in the digital era, this study contributes to a more systematic understanding of universal education as a foundation for digital citizenship and lifelong learning.